Frequent and sex-biased deletion of SLX4IP by illegitimate V(D)J-mediated recombination in childhood acute lymphoblastic leukemia - Meissner, Barbara; Bartram, Thies; Eckert, Cornelia; Trka, Jan; Panzer-Grümayer, Renate; Hermanova, Ivana; Ellinghaus, Eva; Franke, Andre; Möricke, Anja; Schrauder, Andre; Teigler-Schlegel, Andrea; Dörge, Petra; et al. (Human Molecular Genetics, 2014)
Acute lymphoblastic leukemia (ALL) accounts for 25% of pediatric malignancies. Of interest, the incidence of ALL is observed 20% higher in males relative to females. The mechanism behind the phenomenon of sex-specific differences is presently not understood. Employing genome-wide genetic aberration screening in 19 ALL samples, one of the most recurrent lesions identified was monoallelic deletion of the 5' region of SLX4IP. We characterized this deletion by conventional molecular genetic techniques and analyzed its interrelationships with biological and clinical characteristics using specimens and data from 993 pediatric patients enrolled into trial AIEOP-BFM ALL 2000. Deletion of SLX4IP was detected in 30% of patients. Breakpoints within SLX4IP were defined to recurrent positions and revealed junctions with typical characteristics of illegitimate V(D)J-mediated recombination. In initial and validation analyses, SLX4IP deletions were significantly associated with male gender and ETV6/RUNX1-rearranged ALL (both overall P < 0.0001). For mechanistic validation, a second recurrent deletion affecting TAL1 and caused by the same molecular mechanism was analyzed in 1149 T-cell ALL patients. Validating a differential role by sex of illegitimate V(D)J-mediated recombination at the TAL1 locus, 128 out of 1149 T-cell ALL samples bore a deletion and males were significantly more often affected (P = 0.002). The repeatedly detected association of SLX4IP deletion with male sex and the extension of the sex bias to deletion of the TAL1 locus suggest that differential illegitimate V(D)J-mediated recombination events at specific loci may contribute to the consistent observation of higher incidence rates of childhood ALL in boys compared with girls.
EVALuna2:18859